(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Lahore Congress of 1929 had authorized the Congress Working Committee to launch a programme of civil disobedience including non-payment of taxes. In mid-February 1930, at a meeting at Sabarmati Ashram it invested Gandhiji with full powers to launch the Civil Disobedience movement at the time and place of his choice. Gandhiji was already ’disparately in search of an effective formulae’. Besides, his ultimatum of 31 January to Lord Irwin stating the minimum demands in the form of 11 points had been ignored. The only way out left for Gandhiji was civil disobedience. He believed that the Salt tax constituted ’the most inhuman poll tax the ingenuity of man can devise. Therefore, Gandhiji started his famous Dandi march to break the salt law.